2010
DOI: 10.1586/egh.10.74
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-catenin signaling pathway in liver biology and disease

Abstract: The Wnt signaling pathway is an evolutionarily conserved, highly complex signaling pathway that is critical for development, differentiation and cellular homeostasis. The protein β-catenin is the central player in one major arm of the Wnt pathway called the canonical Wnt pathway. As in other organs, the Wnt/β-catenin pathway is critical for liver development. However, recent research suggests that the pathway is also important in liver regeneration, liver metabolism and maintenance of normal function in the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 91 publications
(97 reference statements)
2
67
0
Order By: Relevance
“…In the current study, we report for the first time that maternal exposure to a HF diet programmed the canonical Wnt signaling pathway in the liver of offspring by decreasing the expression of Wnt1 and the protein level of b-catenin. Although the role of specific Wnt genes remains obscure during liver development, the function of canonical Wnt signaling pathway and b-catenin has been confirmed in multiple physiological and pathological aspects of liver, including development, regeneration, growth, and carcinogenesis (Clevers 2006, Behari 2010. Ober et al (2006) identified an important role of Wnt signaling as a positive regulator of liver specification and induction in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we report for the first time that maternal exposure to a HF diet programmed the canonical Wnt signaling pathway in the liver of offspring by decreasing the expression of Wnt1 and the protein level of b-catenin. Although the role of specific Wnt genes remains obscure during liver development, the function of canonical Wnt signaling pathway and b-catenin has been confirmed in multiple physiological and pathological aspects of liver, including development, regeneration, growth, and carcinogenesis (Clevers 2006, Behari 2010. Ober et al (2006) identified an important role of Wnt signaling as a positive regulator of liver specification and induction in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has suggested that the Wnt signaling pathway is critically involved in liver development and postnatal liver homeostasis. In addition, this pathway is also associated with many other important liver functions, such as ammonia and nitrogen metabolism, bile acid homeostasis, drug detoxification and injury recovery (Behari, 2010;Takigawa and Brown, 2008).…”
Section: Wnt/-catenin Pathwaymentioning
confidence: 99%
“…A transgenic mouse model overexpressing -catenin developed severe hepatomegaly (Giles et al, 2003). There are also studies associating -catenin mutations or activation with worsened HCC outcome such as larger tumor size and increased vascular invasion (Behari, 2010).…”
Section: Wnt/-catenin Pathwaymentioning
confidence: 99%
“…Targets to these altered miRNAs mapped onto the Wnt signaling pathway, and we further observed that many components of this pathway were downregulated in the diabetic liver. Besides the well-known functions of Wnt signaling in early development and organogenesis, it plays a role in postnatal liver growth and regeneration, and in the establishment of hepatic zonation (12). However, the Wnt pathway has not been explored extensively in the context of hepatic metabolism.…”
mentioning
confidence: 99%